Enhancement of Gain in L-Band Bismuth-Based Erbium-Doped Fibre Amplifier Using an Un-pumped EDF and Midway Isolator - Chong, W. Y; Harun, S. W; Ahmad, H (2004)
A hybrid L-band erbium-doped fibre amplifier (EDFA) with enhanced gain characteristic is demonstrated without a significant noise figure penalty. It uses a backward C-band amplified stimulated emission from both the ends of a bismuth-based EDFA system to pump an unpumped erbium-doped fibre (EDF) for gain enhancing. The maximum gain enhancement of 4.0 dB is obtained at wavelength 1604 nm with EDF length of 20 m. The gain spectrum is reasonably flat in this amplifier compared with the amplifier without an EDF. The gain varies from 27.4 dB to 30.2 dB at wavelength region 1564-1608 nm with incorporation of 20 m EDF. Noise figure also varies from 6.0 to 7.7 dB at this wavelength region.